Pengaruh Religiusitas, Self Control, Teman Sebaya, Parental Income Terhadap Perilaku Menabung Pada Generasi Z ( Studi Kasus Mahasiswa Pondok Pesantren Al-Mas’udiyyah Blater, Bandungan) - Saputri, Alfina Yulia; Indriasari, Ika; Ervina I, Rr Hawik (Innovative: Journal Of Social Science Research, 2024)
This research aims to determine the influence of religiosity, self-control, peers, parental income on saving behavior in Generation Z (Case Study of Al-Mas'undiyyah Blater Islamic Boarding School Students, Bandungan). This research uses quantitative research methods. The population used in the research were students at the Al-Mas'udiyyah Blater Islamic Boarding School, Bandungan and the sample used was 110 students, using a purposive sampling technique. Data analysis in this study used SPSS for window version 22 software. The results of this study show that there is no influence of religiosity on saving behavior, there is an influence of self-control on saving behavior, peers on saving behavior, and parental income on saving behavior. It can be seen in the Summary table with an Adjusted R square value of 0.755 x 100% = 75.5%.